The Performance of Wayang Orang Sriwedari Surakarta: A Cultural Preservation - Nur Fitria, Tira (LPPM Universitas Terbuka, 2023)
Indonesia is home to a rich cultural heritage, one of which is the art of Wayang Orang in Solo. However, currently, it is facing economic challenges and requires ongoing efforts for preservation. This study investigates the performance of Wayang Orang Sriwedari (WOS) as cultural preservation for tourism in Solo. It is descriptive qualitative. The analysis showed that Surakarta (City of Solo) is a cultural tourism destination with a diverse range of cultures. WOS is one of Solo’s traditional performances. With the tourism slogan “Solo the Spirit of Java”, Surakartais hoped to become a center for the preservation and development of Javanese culture. The art of WOS still survives and holds regular performances during the development of modern art. July 10, 2022, became an important moment for the WOS community for its 112th anniversary. For more than a century, Javanese art and culture associations were able to survive and defend themselves, both in form, content, and management pattern. This art has philosophical, artistic, and moral values and entertainment. WOS is an alternative tourist attraction that can be enjoyed by domestic and foreign tourists. In the development of tourism, some steps for revitalization and preservation by the Surakarta City Government. Hopefully, the beauty and charm of the Sriwedari people’s wayang will continue to shine, enlighten hearts, and preserve Indonesia’s cultural heritage for generations to come.